A Multimodal Analysis in Mustika Ratu Advertisement - Marpaung, Budi Awan; Nurlela (Jurnal Bahasa Inggris Terapan, 2025)
A woman needs cosmetics which is why the researchers are concerned for and care about it. Therefore, the research used multimodal analysis theory by Kress and van Leeuwen (2006) for visual text, generic structure potential (GSP) theory by Cheong (2004), and meta functions of language such as ideational, interpersonal, and textual by (Halliday & Matthiessen, 2004) for verbal text in an ad. The result of the multimodal analysis of the Mustika Ratu advertisement is described in visual coupled with written text. In other words, the goal of this study is to describe the structure of multimodal analysis found in the advertisement. To achieve the research's goal, descriptive qualitative research was used. The source data, which is a print advertisement, was gathered via Google Images, and then reading the text attempted to analyze the advertisement, classifying and analyzing the data according to the verbal and visual texts. Finally, the researchers discovered that the structure of the verbal texts with a sly move (Announcement, Enhancer, Emblem) and the visual texts (Lead, Display, Tag, and Emblem) in the advertisement determines how they can attract and persuade viewers.